2017
DOI: 10.1177/0163443717703793
|View full text |Cite
|
Sign up to set email alerts
|

‘I’d Double Tap That!!’: street art, graffiti, and Instagram research

Abstract: Recent scholarship into the uses of social media has opened up productive ways of thinking about the dynamic relationship between user-generated content and new forms of sociality and social practice. However, compared with Twitter and Facebook, the photo- and video-sharing platform Instagram has received relatively little scholarly attention. Instagram is only the latest in a complex media history that has shaped a range of social practices, including graffiti and street art. This article considers the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 23 publications
2
43
0
1
Order By: Relevance
“…In what MacDowall and de Souza (2018) call ‘photostream’, images ‘appear as fleeting digital objects in a continually updated visual flow’ (p. 9). Given that images are ‘largely viewed for their immediate visual impact on a distracted viewer rather than as an object for careful consideration or analysis’ (MacDowall and de Souza, 2018: 9), the very visual quality of images matters in order to attract more viewers and followers. Instagram photos must and, in fact, have strong visual components and qualities, and images of tourism and place are no exception.…”
Section: Digital Wall: ‘Pretty Place’ Images On Instagrammentioning
confidence: 99%
See 1 more Smart Citation
“…In what MacDowall and de Souza (2018) call ‘photostream’, images ‘appear as fleeting digital objects in a continually updated visual flow’ (p. 9). Given that images are ‘largely viewed for their immediate visual impact on a distracted viewer rather than as an object for careful consideration or analysis’ (MacDowall and de Souza, 2018: 9), the very visual quality of images matters in order to attract more viewers and followers. Instagram photos must and, in fact, have strong visual components and qualities, and images of tourism and place are no exception.…”
Section: Digital Wall: ‘Pretty Place’ Images On Instagrammentioning
confidence: 99%
“…Second, the filter function of Instagram accentuates aesthetic qualities of IMV, even further obscuring existing social conditions of the neighborhood. ‘The most visually distinctive feature of Instagram’s platform vernaculars is its vintage-inspired preset filters that mimic the washed-out, dreamy aesthetic and mood of analogue photography’ (MacDowall and de Souza, 2018: 8). There are over 40 built-in filters, such as Clarendon, Juno, and Ludwig that adjust color, saturation, contrast, shadow, brightness, vividness, intensity, tone, and luminance of images.…”
Section: Digital Wall: ‘Pretty Place’ Images On Instagrammentioning
confidence: 99%
“…The portrayal of a consistent and distinctive style identity was particularly important to the most career-minded participant, who had the highest follower numbers at 54k. Jura (25) chose to edit all her images before uploading these to Instagram; moving away completely from the realtime appeal that is usually associated with the platform, where an influencer might shoot, filter and post an image immediately (Song, 2016;MacDowell and de Souza e Silva, 2018). She felt she portrayed a realistic version of her offline style by showing herself in and around her hometown of Glasgow in the clothes she was wearing that day: "just putting on jeans and a t-shirt and a blazer -that literally it is my day.…”
Section: Identity Evolution On Instagrammentioning
confidence: 99%
“…1 4 , I s s . 2 , 2 0 2 0 street art as a communicative space in the Middle East dates back to the Lebanese civil war and the first Palestinian intifada in Gaza and has been widely deployed as a protest aesthetic, a counter-narrative tool, and a community-centered art form in the region (Kraidy 2016a;MacDowall and de Souza 2018;Sinno 2017;Peteet 1996;Gruber 2008). Scholars studying the use of street art in conflict situations in Northern Ireland, Palestine, and Egypt have suggested that street art in conflict zones becomes "a means of political resistance by envisioning competing futures, inscribing memory and critically commenting on political events" (De Ruiter 2015, 582).…”
Section: Tactical and Participatory Mediamentioning
confidence: 99%